Classification of environments based on correlations of yield in spring bread wheat - S. B. Lepekhov (Труды по прикладной ботанике, генетике и селекции)
Background. Genotype–environment interaction complicates selection of lines in plant breeding. Researchers have developed different ways to classify environments to mitigate its effect. The use of correlation analysis between yields of cultivars grown in different environments was earlier proposed for classification of these environments.The aim of this research was to classify years on the basis of correlations of the yields in a specially selected set of spring bread wheat cultivars and to verify the application of such classification to breeding material in different nurseries.Materials and methods. The material for the experiment included cultivars, lines and breeding samples from the collection nursery, competitive variety trials, and the nursery for segregating populations, respectively. The experiments were conducted from 2010 through 2017. The correlation analysis between the yields of 19 marker cultivars of different ecogeographic origin was used as the basis for the classification of years. The calculated correlation parameters for the yields of marker cultivars and those of the breeding material in nurseries for the same pairs of years were compared using the Mann–Whitney U-test.Results. The years under consideration were classified into three groups: 1) 2010 and 2013; 2) 2011, 2012 and 2014; 3) 2015, 2016 and 2017. Correlations between the yields of the marker cultivars showed no significant differences from those of the genotypes from other nurseries across the analyzed years. Consequently, the classification of years based on the reactions of marker cultivars can be justifiably extended onto other breeding material.Conclusion. It is suggested to select and use a set of marker cultivars in multi-environment trials to obtain additional information about target environments and make more informed decisions on culling plant breeding materials.